Estimating the effects of the "flight to quality", with an application to German bond yields and interest payments - Claire A. Boeing-Reicher; Jens Boysen-Hogrefe (Kiel Institute for the World Economy (IfW), 2017)
Recent calculations have suggested that the German federal government has saved roughly EUR 90-100 billion, cumulatively, due to low bond yields since the onset of the Euro crisis. In order to determine the contribution of the "flight to quality" to this sum, we define the flight to quality as a factor which has caused German bond yields and crisis country bond yields to move in opposite directions. Estimates show that only a small share is due to the flight to quality. Comparison with other approaches suggests that our factor approach is a promising way to look at the flight to quality.
Keywords: C32; C58; G12; 330; flight to quality; Euro crisis; bond yields; Germany; factor model